(3GdJaGhVs - (3eMeO(B, (3GdUjQajs ((3GdGScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2007)
(3jhLO aj gPG GdcJGH eaghe GdJaGhV , GdGJUGd GdGbfGYj hGdYedjI GdJaGhVjI , GdhbJ hGdYedjI GdJaGhVjI , GSJQGJLjGJ GdJaGhV , GdJfGRYGJ hGdeLGedGJ hGdYhGWa aj GdYedjI GdJaGhVjI , GdJYGed eY GdNUe , GfgGA GdeaGhVGJ , eNJHQGJ hMGdGJ YedjIs
(3HjHdjhZQGajG(B: (3U(B. 301s
Keywords: (3GdEJUGds; (3GdJMcjes; (3GdeaGhVGJs